Computer assisted surgical planner for craniofacial reconstruction - imaging techniques - Rana, Mohammad Azam; Setan, Halim; Majid, Zulkepli; Chong, Albert K. (IEEE Computer Society, 2006)
Computer Tomography (CT)and Magnetic Resonance Imagery (MRI)have had an enormous impact in medicine.Using medical imagery,Computer Assisted Surgery (CAS)systems decrease the invasiveness of surgical procedures,increase accuracy and facilitate surgical planning and analysis.Craniofacial anomalies and fine anatomic details of facial traumic injuries can be well studied with such imaging techniques.This research is focused on reconstruction of human hard/soft tissues and anthropometric landmarks for craniofacial surgery. The data capture devices used include CT scanner,3D Laser Scanner and Close Range Photogrammetry.The visualization of soft tissue superimposed on hard tissue,display of tissue with varying opacity,and cutting of tissues for detailed analysis and planning has been demonstrated in this paper.